STRENGTHENING LITERACY AND NUMERACY SKILLS OF PRIMARY SCHOOL STUDENTS THROUGH EDUCATIONAL GAMES - Pamungkas, Arimbi; Soraya, Rahayu (Waniambey: Journal of Islamic Education, 2024)
Strengthening literacy and numeracy skills in Primary school students is a fundamental aspect closely related to classroom learning. This study aims to describe various educational games that can enhance students' literacy and numeracy skills. The method used is a literature study, where data is obtained from books and scientific articles. The research results show that using educational games is efficacious in improving Primary school students' literacy and numeracy skills. Educational games also motivate students to understand literacy and numeracy in an enjoyable manner. Educational game-based learning media attract students' attention and encourage them to learn interactively and communicatively. Implementing games in learning helps students better understand literacy and numeracy concepts. One example of an educational game that can be used is the crossword puzzle, which is proven to be engaging and helps students remember vocabulary and general knowledge more efficiently. In the digital era, literacy and numeracy are essential skills that must be introduced early on. Educational game-based learning media is validated and deemed suitable for teaching, with an average validation rate of 74% and a positive student response rate of 80%. In conclusion, using educational games effectively enhances Primary school students' literacy and numeracy skills, and teachers must continue to innovate in the learning process to improve these skills